2012
DOI: 10.1002/msc.1023
|View full text |Cite
|
Sign up to set email alerts
|

Conversion Rates and Perceived Barriers to Referral: Views of Extended Scope Physiotherapists in the Primary Care Setting

Abstract: Aims A questionnaire survey of primary care musculoskeletal extended‐scope physiotherapists (ESPs) was undertaken to determine information about their conversion rates and referral barriers, with regard to radiological and consultant referrals. Method A sample of 200 musculoskeletal ESPs classified as having a speciality in orthopaedics and working in primary care were recruited via the ‘ESP Professional Network’. Results A total of 100 (50%) responses were received. Forty‐seven per cent of primary care ESPs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The second study (Griffiths et al, ) described the results of onward referrals from a primary care‐based ESP service into specialist secondary care services, reporting a 74% surgical conversion rate from those cases referred.…”
Section: Resultsmentioning
confidence: 99%
“…The second study (Griffiths et al, ) described the results of onward referrals from a primary care‐based ESP service into specialist secondary care services, reporting a 74% surgical conversion rate from those cases referred.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the use of the term ‘triage’ in the context of the management of patients with an orthopaedic/musculoskeletal complaint, our thematic analysis demonstrated that this word has a variety of meanings, descriptions and definitions and is applied within, different health care settings, in a variety of methods. Of the 45 papers, eight did not provide adequate descriptions of triage and were therefore removed from the thematic analysis [16–23].…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study may support the relocation of APP services to primary care, as in the UK and Sweden [ 24 , 25 ]. However, close proximity of the Consultant and clinical investigations in hospitals may alleviate any potential barriers to Consultant referrals [ 26 ], and concerns of delayed patient management [ 27 ]. Co-location of APP and Consultant clinics may also reduce referrals to Consultant services, as discussion on clinical management can occur on the day of the appointment.…”
Section: Discussionmentioning
confidence: 99%